PENSERTIPIKATAN TANAH WAKAF YANG BERASAL DARI TANAH ULAYAT DI MINANGKABAU DALAM RANGKA MEWUJUDKAN KEPASTIAN HUKUM - Yunimar . (Normative Jurnal Ilmiah Hukum, 2017)
Wakaf land is a land that is separated forever for religious purposes, such as for mosques, schools, orphanages, and others. According to the law number 41 of 2004 on Waqaf, each land must be certified wakaf, in order to materialize the legal certainty. Wakaf land grants derived from ulayat land in Minangkabau have not been done due to the ignorance of the community about the benefits of the wakaf land certificates, so further recognition is needed